Pengaruh Aplikasi Kalium Permanganat (KMnO4) terhadap Umur Simpan Buah Pisang Kepok (Musa paradisiaca formatypical ABB Group) - UYUN FITRI MALINDA; MADE SUDIANA MAHENDRA; I MADE SUKEWIJAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Effect of Application of Potassium Permanganate (KMnO4) on the Shelf Life of Kepok Banana Fruit (Musa paradisiaca formatypical ABB Group) Banana is one of the fruit that is widely cultivated in Indonesia. The potential of large banana production is quite prospective to be developed as a local food source. This research aims to determine the effect of application of potassium permanganate on the shelf life of kepok banana fruit. Research conducted in Agronomy and Horticultural Laboratories and Ecophysiology Laboratory of the Faculty of Agriculture, Udayana University. The research was conducted in June-October 2019. The research was designed by randomized complete block design (RCBD) single factor consisting of 6 treatments i.e. K0 = control (without oxidizing materials), K1 = 10 g oxidizing materials, K2 = 30 g oxidizing materials, K3 = 50 g oxidizing materials, K4 = 70 g oxidizing materials, K5 = 90 g oxidizing materials. The observation is done in a destructive manner (content of vitamin C, total dissolved solids, and hardness) and non destructive (shelf life, weight shrinkage, respiration, color). The results showed that the longest shelf life of the fruit (27 days of storage) was on the K1 (10 g oxidizing materials) and K2 (30 g oxidizing materials) treatment. The smallest weight in the treatment of K1 (10 g Oxidizing materials) and K2 (30 g Oxidizing materials) on the 21st day reaches 0,006% and 0,007%. K2 treatment indicates the lowest respiration rate rate at 9 after treatment (AT) is 4,90 mg CO2/kg/hr. KMnO4 treatment does not give real influence on the hardness, content of vitamin C, PTT except on 21 AT, and the skin color of the fruit except on 27 AT.